Threat appraisal, emotional contagion, and Fear of COVID-19: Revision of the Extended Parallel Process Model - Prince, M.; Kim, Y. (Journal of Applied Social Science, 2023)
Fear of COVID-19 has been understandably widespread, given continual exposure to dire information from pandemic media coverage and interpersonal communications. The present study addresses a limitation of the extended parallel process model in predicting fear of COVID-19 by inclusion of the concept of emotional contagion. The main gap in the literature is filled by the study’s distinctive contribution that broadens and upgrades the extended parallel process model. The model is extended by its integration with the theory of emotional processing. The study is based on a national panel of adults (N = 206). The methods include path modeling by SmartPLS. In addition, multigroup analyses examine overall model differences between gender classifications. Findings and conclusions can be used to minimize excessive fear, and at the same time to promote confidence in following official public guidance and protective regulations to cope with the pandemic. © The Author(s) 2023.
Keywords: cognitive; dept.mkt; emotional contagion; fear; motivation; peer-reviewed; threat appraisal

Information technology adoption and the growth of nonemployer businesses - Kim, Y.; Thompson, E. (Journal of Economics and Management Strategy, 2024)
The growth of nonemployer businesses as a share of the working-age population has been little studied relative to the decline of employer business rate in the United States. We show that local labor markets specializing in routine task-intensive jobs have experienced a higher adoption of information technology as well as the growth of nonemployer businesses primarily through increasing self-employment in nonroutine manual task-intensive jobs that are less frequently outsourced to business service firms. © 2024 Wiley Periodicals LLC.
Keywords: dept.eco; peer-reviewed